Self-Esteem of Adolescents with ASD From Families with Low Financial Status During The SARS-Cov-2 Pandemic - Anna GAGAT-MATUŁA (Communications of International Proceedings, 2021)
In a Polish study conducted by the JiM Foundation on the situation of people with ASD and their families, it was shown that the income of most parents and carers (38%) was in the range of PLN 500-1,000 per family member, while 36% declared an income of PLN 1,000-PLN 1,500 per person, 19% - income above PLN 1,500 per person, and 7% live below the statutory poverty line, earning an income per family member of below PLN 500. Most respondents (59%) described their financial situation as average, while according to 27% of respondents it was good, and according to 14% - bad (Szymańska & Warszawa, 2017). The probability of financial problems in families of children with ASD is much higher and is associated with a family incurring non-reimbursed expenses for treatment or therapy, along with a relatively low income (Sharpe & Baker, 2007), while the financial support received by families of people with ASD is often assessed by parents as insufficient (Jaranowska, 2016). In families with a disabled person, the risk of poverty increases, and families in which the problem of disability affects a child are particularly vulnerable (Igielski & Żak, 2019).